The Effects of Climate Change on Forest Insect Disturbance in South Korea : Challenges and Prospects (영문판) - 안현진 (기후변화에 따른 산림병해충 영향과 대응과제, 2019)
Climate change is a serious global issue. It has occurred gradually over a long period but accelerated after the industrial revolution. Rapid climate change can cause great damage to not only humans but also the entire planet. In response to climate change, countries around the world have signed the Kyoto Protocol and the Paris Convention and are carrying out various national countermeasure programs to cope with climate change. Climate change is also a major concern in the forest sector. It can change the benefits of forests to humans or even cause forests to damage humans. One of the damages by forest due to climate change is the emergence of forest pests. As such, studies on the relationship between climate change and the occurrence of forest pests are ongoing in steps, but there are only few studies of the economic impact of forest pests on climate change. This study presents a method to measure the impact of damage by forest pest as the result of climate change. Specifically, it establishes the damage function with direct and indirect factors affecting the damage by forest pests and predicts the future damage rate according to future climate change. Using the predicted damage rate, it examines the impact of pests on the incomes of and the forest management decision by the forest owner by analyzing the change of future income from forest management, the change of tree forest cutting age, and the control efficacy. Lastly, it conducts a policy experiment to propose an effective forest pest management plan.